Length-weight relationship and relative condition factor of Yellowstripe scad, Selaroides leptolepis (Cuvier, 1833) in the Visayan Sea, Philippines - Quin Yudelmo Clarito (Aceh Journal of Animal Science, 2021)
The length-weight relationship (LWR) and relative condition factor (Kn) are essential biometric tools in fishery studies since they provide information about the fish's growth, condition, and suitability in its habitat. The LWR of 680 samples of Selaroides leptolepis or yellowstripe scad collected from commercial trawls fishing in the Visayan Sea was studied to determine its growth condition. The results indicated that S. leptolepis exhibited an isometric growth (b = 3.023), indicating an equal growth rate of the fish's length size and body weight.  The relative condition factor (Kn) values of the studied species fluctuated between 0.95 to 1.10 from November 2018 to October 2019 study period. The dry season had been observed that might influenced the Kn values 1, which indicated a state of well-being of yellowstripe scad during this season. The current study would provide baseline data about LWR and the relative condition factor of S. leptolepis in the Visayan Sea. These data are valuable for establishing a monitoring and management system for this fish species.